2018
DOI: 10.1159/000499960
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Lipopolysaccharide-Induced Intrauterine Inflammation in Near-Term Rabbits Leading to Newborn Neurobehavioral Deficits

Abstract: Background: Chorioamnionitis from ascending bacterial infection through the endocervix is a potential risk factor for cerebral palsy. Tetrahydrobiopterin, an essential cofactor for nitric oxide synthase (NOS) and amino acid hydroxylases, when augmented in the fetal brain, prevents some of the cerebral palsy-like deficits in a rabbit hypoxia-ischemia model. Objectives: To study the effect of lipopolysaccharide (LPS)-induced intrauterine inflammation in preterm gestation on motor deficits in the newborn, and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…In addition, concerns about the usefulness of the intrauterine administration of LPS as a model for ascending infection-induced preterm birth in women were raised by a compelling study that found systemic, but not intravaginal treatment induce preterm birth in mice (141). Except for introduction of LPS into the endocervix (144), which breaches the luminal epithelial immune interface, there is consistent evidence for systemic inflammatory drive of preterm birth. By example, the importance of myeloid-derived immune cells and activities for cervix remodeling was emphasized in a recent study in mice that used antibody treatment to suppress the cytokine granulocyte-macrophage colony stimulating factor (GM-CSF) and block LPS-induced preterm birth (145).…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 99%
“…In addition, concerns about the usefulness of the intrauterine administration of LPS as a model for ascending infection-induced preterm birth in women were raised by a compelling study that found systemic, but not intravaginal treatment induce preterm birth in mice (141). Except for introduction of LPS into the endocervix (144), which breaches the luminal epithelial immune interface, there is consistent evidence for systemic inflammatory drive of preterm birth. By example, the importance of myeloid-derived immune cells and activities for cervix remodeling was emphasized in a recent study in mice that used antibody treatment to suppress the cytokine granulocyte-macrophage colony stimulating factor (GM-CSF) and block LPS-induced preterm birth (145).…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 99%
“…cDNA sequencing was performed using a 96-capillary automated DNA sequencer (Applied Biosystems 3730XL) and confirmed by alignment with the predicted sequences at GenBank. The rabbit gene sequence and GenBank ID has recently been published [11].…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was purified from the cortex, cerebellum, and thalamus using the PureLink RNA Mini Kit (Life Technologies, Grand Island, NY) as done previously [11]. Samples were chosen in pairs of either high or low tetrahydrobiopterin levels.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of this, the fetus can mount an inflammatory response. For example, intrauterine immune activation by LPS augments IL-1β, IL-6 and IL-8 while reducing TNF-α and TGF-β in the fetal brain [ 140 ]. Similarly, intestinal NF-κB function, as well as expression of NF-κB, IL-1β and TNF-α, augment in newborns that receive Escherichia coli solution or E. coli -fermented formula [ 141 ].…”
Section: Important Immune Mediators During the Neonatal Periodmentioning
confidence: 99%